A Review of Fiqh and Compilation of Islamic Law on the Marriage Status of Apostate Couples: A Case Study of Kayu Kebek Village, Tutur District, Pasuruan Regency - Nahar Luthfillah, Sulthon (Department of Comparative Mazhab Comparative, Fakulty of Shariah and Law, 2025)
The marital status of a partner who is an apostate or changes religion in marriage in Law No. 1 of 1974 does not involve the breaking of a marriage bond. But in the Fiqh of a partner who apostates, the marriage bond is automatically annulled or the marriage bond is dissolved. According to Fiqh experts, if one of the partners, be it husband or wife, changes religion or apostates, then the marriage is said to be fasakh or the breaking of their marriage bond. In the Compilation of Islamic Law, article 115 states that divorce can only be carried out in front of a religious court, if they do not file for divorce in court then the marriage is still considered valid. As is the case in Kayu Kebek village, Tutur subdistrict, Pasuruan regency. In Kayu Kebek village there are several couples who change religions or apostatize during marriage. The main question in this research is what is the marital status of couples who have apostatized from the perspective of Islamic Law and the Compilation of Islamic Law? To answer this question, the author uses a normative juridical approach by using field research to obtain these data. The author uses two data sources, namely primary data sources obtained from interviews while secondary data obtained from laws. Marriage, KHI Hadith and rules of Fiqh.